Second concert of the Salzburg Festival, August 6, 1939, with the Vienna Philhamonic performing the Ninth Symphony - Wiener Philharmoniker:::Creator:::::::::::: (Salzburg; Austria, 2020)
Program for a performance by the Vienna Philharmonic under the direction of Haus Knappertsbusch of Beethoven's Ninth Symphony at the Salzburg Festival on August 6, 1939. Includes program notes in German, English, and French.